FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PARTISIPASI KADER DALAM PENYELENGGARAAN KELAS IBU HAMIL DI KELURAHAN NGESREP KOTA SEMARANG - Linda Agustinawati; Besar Tirto Husodo; Syamsulhuda Budi Musthofa (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2017)
Antenatal Class is a group learning facilities about maternal health that can not be separated from the role of cadres. Based on the result of the research, there were 52,3% respondents who actively participated in the implementation of Antenatal Class and 42,7% respondents less actively participated in the implementation of Antenatal Class. The purpose of this research is to know the factors related to the participation of cadres in the implementation of the Antenatal Class. The purpose of this study was to analyze factors related to cadre participation in the implementation of Antenatal Class. The hypothesis proposed that there is a relationship between independent variables and dependent variable in research. Subjects in this study were posyandu cadres in the work area of Ngesrep Village amounted to 65 people. The method of data collection used is a questionnaire. This study was using univariate, bivariate, and multivariate data analysis. Data analysis technique used is a Chi-Square test (significance level=0,05). The results showed that factors related to the participation of cadres in the implementation of Antenatal Class were age (p=0,034), attitude (p=0,000), availability of information (p=0,004), family support (p=0,000), community support (p=0,019), and health officer support (p=0,023). The variables that influence the participation of cadres in the implementation of Antenatal Class is family support (p=0,001) and (OR=30,985). From this research, it can be concluded that there are 6 of 13 related dependent variables and 1 variable influencing the participation of cadres in the implementation of Antenatal Class and most respondents (52%) actively participate in the implementation of Antenatal Class. Suggestions for this research are the need for support from family either emotional support, instrumental, or award.